2019
DOI: 10.31703/gssr.2019(iv-i).22
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Based Effect of Cyber Bullying on Academic Achievement and Behavior of Students at Higher Secondary Level

Abstract: The purpose of this research is to discover the effect of cyber bullying on students academic achievement and their behavior. The objective of the research was to find out the academic achievement affected by cyberbullying and behavior of students on gender basis at higher secondary school level. Through random sampling technique, 2160 students and 48 teachers from 6 districts were selected. Questionnaires and interviews were used for data analysis using descriptive statistics and inferential statistics. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…Karakus et al (2022) also concluded that students who experienced bullying victimization are associated with more significant negative outcomes. Moreover, no relevant differences by gender were observed, a result that is consistent with others studies (Begum et al, 2019;Van der Worf, 2014). Van der Werf (2014) found that the effects of bullying show differences in terms of age (stronger in younger students in the short term), but no significant differences in terms of gender.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Karakus et al (2022) also concluded that students who experienced bullying victimization are associated with more significant negative outcomes. Moreover, no relevant differences by gender were observed, a result that is consistent with others studies (Begum et al, 2019;Van der Worf, 2014). Van der Werf (2014) found that the effects of bullying show differences in terms of age (stronger in younger students in the short term), but no significant differences in terms of gender.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies had already confirmed these results (Karakus et al, 2022;Lee et al, 2018;Yu & Zhao, 2021). Analyzing the link between bullying victimization and test scores, but differentiating by student gender, we found that there were no major differences between males and females, which was in line with the findings of other authors (Begum et al, 2019;Van der Werf, 2014). Only in the case of mathematics (a subject where males traditionally get better results, OECD, 2015) did a male victim of bullying score 1.89 points less than a female who had the same values in the index of bullying victimization, all the other factors being equal.…”
Section: Estimations Of Students' Outcomes and Bullying Victimizationsupporting
confidence: 92%
See 1 more Smart Citation